Dynamics of Organizational Culture: The Influence of Manipulative Behavior and Social Interaction in Private Universities - Yulianti, Welly; Wardi, Yunia; Sulastri, Sulastri; Rino, Rino (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to identify the influence of manipulative behavior and social interaction on organizational culture. Referring to previous literature and research, manipulative behavior can change organizational culture, this is also based on social interaction within the organization. The quantitative method was chosen to provide an analysis related to manipulative behavior and social interaction on organizational culture by involving a sample of 140 people. The results of this study indicate that manipulative behavior carried out ethically can improve teamwork and communication, and strengthen organizational culture. However, balance is very important, because too much manipulation can have a negative impact. These findings are expected to enable managers to develop strategies that balance ethical manipulation and positive work culture.